SEMANTIC AND PRAGMATIC FEATURES OF THE SPEECH ACT OF WARNING IN FRENCH AND UZBEK - Zufarova Sevara Muratdjanovna (International Journal of Literature and Language Studies, 2026)
This paper offers a contrastive study of the semantic and pragmatic properties of the speech act of warning in French and Uzbek. The aim is to identify the illocutionary force of warnings, the interplay between threat and care, and face-saving strategies as encoded through modality, evidentiality, and conventionalized formulas. Methodologically, the analysis combines speech act theory, pragmatic inference, and discourse-based examination of situationally sampled oral and written interactions, grouped by risk type and participant roles. The novelty lies in modeling warning as a dual-purpose act that both prevents harm and distributes responsibility, while demonstrating that French tends to rely more on epistemic mitigation and indirectness, whereas Uzbek shows more systematic social indexing through respect, distance, and hierarchy-sensitive forms. The findings contribute to translation studies, intercultural pragmatics, and the design of pragmatically informed teaching resources for professional communication.